Gambaran kualitas dan mutu radiograf - Alongsyah Zulkarnaen Ramadhan; Suhardjo Sitam; Azhari Azhari; Lusi Epsilawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The study is aimed to give further explanation and understanding of radiograph quality assurance based on scientific literatures. Literature Review: A radiograph’s quality can be assessed based on the produced image itself. The radiograph must meet the standard values to be interpreted by practitioners and radiologists. There are various kinds of standard value of a radiograph that should be met before doing an interpretation, therefore a review is needed to assess the quality of a radiograph. This literature will discuss how to assess the quality of a radiograph. Based on the review of previous literatures, differences have been found between one quality assessment and another, so that the quality of radiograph is fulfilled. Conclusion: A radiograph has many aspects to be assessed to determine its quality.